KONTRIBUSI KOMITE SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM DI MTsN VII KOTO PADANG SAGO KABUPATEN PADANG PARIAMAN - Fatimah Fatimah (Program Pascasarjana UMSB, 2018)
This study aims to describe the contribution of the School Committee as a consideration, support, controller, and liaison in improving the quality of PAI at MTsN VII Koto Padang Sago. This study uses a descriptive qualitative approach. Sources of research data include: School Committee, Head and Deputy Head and teacher assembly of MTsN VII Koto Padang Sago. Data collection techniques used include observation, questionnaire and documentation study. Data analysis uses inductive analysis. The results of this study indicate that the contribution of the School Committee as a consideration, controller and liaison has been good, while the School Committee's contribution as a supporter is considered sufficient. For this reason, the School Committee is expected to improve understanding of its duties and roles and improve coordination between the committee members.